2013
DOI: 10.1001/jamadermatol.2013.6255
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Events Associated With Mohs Micrographic Surgery

Abstract: Mohs micrographic surgery is safe, with a very low rate of adverse events, an exceedingly low rate of serious adverse events, and an undetectable mortality rate. Common complications include infections, followed by impaired wound healing and bleeding. Bleeding and wound-healing issues are often associated with preexisting anticoagulation therapy, which is nonetheless managed safely during MMS. We are not certain whether the small effects seen with the use of sterile gloves and antiseptics and antibiotics are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
1
7

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 154 publications
(81 citation statements)
references
References 16 publications
4
69
1
7
Order By: Relevance
“…Ett sammendrag og tre fulltekstartikler ble lest. To artikler ble inkludert (12,13). Søkestrengen «gloves and wound repair and infection» ga 23 treff.…”
Section: Kunnskapsgrunnlagunclassified
See 3 more Smart Citations
“…Ett sammendrag og tre fulltekstartikler ble lest. To artikler ble inkludert (12,13). Søkestrengen «gloves and wound repair and infection» ga 23 treff.…”
Section: Kunnskapsgrunnlagunclassified
“…Det ble også funnet fire observasjonsstudier over sterile eller rene hansker og sårinfeksjon ved småkirurgi. De ble alle gjort på et annet fagområde enn allmennmedisin (dermatologi) (13,16,22,23). Den største studien med over 20 000 pasienter viste en forskjell i infeksjonsfrekvens (13), mens en annen gjorde det samme for større lappeplastikker, men ikke mindre eksisjoner (22).…”
Section: Tabellunclassified
See 2 more Smart Citations
“…Studies have shown that, for some hand surgery procedures, the sterile drape is sufficient, does not increase the risk of infection, and reduces the cost by four times or more. 30 , 31 , 32 , 33 …”
Section: Sterile Surgical Drapes For Simple Casesmentioning
confidence: 99%